2019
DOI: 10.4274/tjcd.galenos.2019.78857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laparoscopic Embedding Technique and Other Techniques for Appendiceal Stump Closure

Abstract: Amaç: Akut apandisit tüm dünyada en sık görülen cerrahi acil durumdur. Laparoskopik apendektomi akut apandisit ameliyatlarında yaygın olarak kullanılmaktadır. Apendiks güdüğünün kapatılmasında birçok teknik kullanılmıştır. Çalışmamızda, laparoskopik gömme tekniğinin etkinlik ve güvenilirliğini araştırmayı amaçladık. Yöntem: Temmuz 2017-Aralık 2018 tarihleri arasında akut apandisit için apendiks güdüğünün kapatılmasında laparoskopik gömme yöntemi kullanılan hastalar dahil edildi. Fizik muayene, laboratuvar test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Anyway, using endo-loops can reduce the cost of the surgery about 10 times, and also eliminates the risk of creating ileus from staples slipped into the abdomen (11,21,23) . Some studies have also reported that in open appendectomy closure of AS is successfully applied in the laparoscopy technique by ligating AS with a suture, passing it through PSS in the cecum and inverting it into the cecum (24,25) . In our retrospective clinical study, the AS was safely closed using this method, and no stump leak was observed in any of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, using endo-loops can reduce the cost of the surgery about 10 times, and also eliminates the risk of creating ileus from staples slipped into the abdomen (11,21,23) . Some studies have also reported that in open appendectomy closure of AS is successfully applied in the laparoscopy technique by ligating AS with a suture, passing it through PSS in the cecum and inverting it into the cecum (24,25) . In our retrospective clinical study, the AS was safely closed using this method, and no stump leak was observed in any of our patients.…”
Section: Discussionmentioning
confidence: 99%